Infinite detail - Maughan, Tim, 1973- (Farrar, Straus and Giroux, 2019)
BEFORE: In Bristol<U+2019>s center lies the Croft, a digital no-man<U+2019>s-land cut off from the surveillance, Big Data dependence, and corporate-sponsored, globally hegemonic aspirations that have overrun the rest of the world. Ten years in, it<U+2019>s become a center of creative counterculture. But it<U+2019>s fraying at the edges, radicalizing from inside. How will it fare when its chief architect, Rushdi Mannan, takes off to meet his boyfriend in New York City<U+2015>now the apotheosis of the new techno-utopian global metropolis? AFTER: An act of anonymous cyberterrorism has permanently switched off the Internet. Global trade, travel, and communication have collapsed. The luxuries that characterized modern life are scarce. In the Croft, Mary<U+2015>who has visions of people presumed dead<U+2015>is sought out by grieving families seeking connections to lost ones. But does Mary have a gift or is she just hustling to stay alive? Like Grids, who runs the Croft<U+2019>s black market like personal turf. Or like Tyrone, who hoards music (culled from cassettes, the only medium to survive the crash) and tattered sneakers like treasure.